Fake news, media credibility and trust on institutions - Syed Abdullah Idid, Syed Arabi (2019)
Community leaders often speak about the merits and significance of Trust as Trust is deemed fundamental to the workings of institutions in society. Trust is researched in management, politics, sociology, communication and in other subjects but the underlying reasons for the lack of trust are still far from satisfactory. In the absence of trust, society will be presented with mistrust, a situation breeding cynicism and scepticism. Trust is studied at the micro and also at the macro level. Business needs to give trust to the customers that the product and services made available are reliable, as much as the politicians have to sell their performance to gain the trust of their voters during elections. The role of public relations is therefore important for its role in building trust between the organisation it represents and the community that it is in engagement. Recent research has shown how much trust Malaysians have placed in the social and political institutions to endear themselves to the general public. The present day Trust has been challenged by false accusations and, of late, of fake news. Many crises have been arisen due to the dissemination of fake news. This is something that public relations can do through its various programmes and research to minimise or to overcome the negative effects of fake news and thereby improve the Trust in their organisation and also in the various social and political institutions.